Integration of AFLPs, SSRs and SNPs markers into a new genetic map of industrial chicory (Cichorium intybus L. var. sativum). Issue 1 (23rd October 2013) - Muys, Céline; Thienpont, Claire‐Noëlle; Dauchot, Nicolas; Maudoux, Olivier; Draye, Xavier; Cutsem, Pierre Van; Debener, T.
Abstract A chicory genetic map of 1208 cM has been created using 247 F2 plants and 237 markers (170 AFLP, 28 SSR, 27 EST‐SNP and 12 EST‐SSR). This map covers 84% of the chicory genome. The chicory‐genic‐markers‐associated sequences were used to find potential orthologs in mapped lettuce ESTs from the Compositae Genome Project Database. Twenty‐seven putative orthologous pairs were retained, pinpointing seven putative blocks of synteny that covered 11% of the chicory genome and 13% of the lettuce genome, opening new perspectives for the analysis of these two species.